Synthesis and biological evaluation of 3β-O-neoglycosides of caudatin and its analogues as potential anticancer agents. (15th January 2022) - Li, Xiao-San; Chen, Tang-Ji; Xu, Zhi-Peng; Long, Juan; He, Miao-Ying; Zhan, He-Hui; Zhuang, Hai-Cai; Wang, Qi-Lin; Liu, Li; Yang, Xue-Mei; Tang, Jin-Shan
Graphical abstract: Highlights: A series of 3 β -O-neoglycosides of caudatin and its analogues were synthesized. Most of peracetylated 3β-O-monoglycosides demonstrated moderate to significant antiproliferative activities. Compound 2k exhibited the highest antiproliferative activity against HepG2 cells with an IC50 value of 3.11 μM. Compound 2k could induce HepG2 cell apoptosis and cell cycle arrest at S phase in a dose dependent manner. Abstract: In order to study the structure–activity relationship (SAR) of C21 -steroidal glycosides toward human cancer cell lines and explore more potential anticancer agents, a series of 3 β -O-neoglycosides of caudatin and its analogues were synthesized. The results revealed that most of peracetylated 3β-O-monoglycosides demonstrated moderate to significant antiproliferative activities against four human cancer cell lines (MCF-7, HCT-116, HeLa, and HepG2). Among them, 3β-O-(2, 3, 4-tri-O-acetyl-β-L-glucopyranosyl)-caudatin (2 k ) exhibited the highest antiproliferative activity aganist HepG2 cells with an IC50 value of 3.11 μM. Mechanical studies showed that compound 2k induced both apoptosis and cell cycle arrest at S phase in a dose dependent manner. Overall, these present findings suggested that glycosylation is a promising scaffold to improve anticancer activity for naturally occurring C21 -steroidal aglycones, and compound 2 k represents a potential anticancer agent deserved further investigation.